Parlamento Andino presente en la feria Innopolis - Parlamento Andino (Parlamento Andino, 2015)
La migración internacional caracterizada por el flujo de personas que se movilizan de un pais a otro con el fin de cambiar de residencia habitual

International migration characterized by the flow of people who move from one country to another in order to change their habitual residence
Andean Parliament present at the Innopolis fair
Keywords: Parlamento Andino; Comunidad Andina